AI Management System ISO 42001 and SDG for Impacts - Yeung, Shirley M.C. (Journal of Ecohumanism, 2025)
The purpose of this paper is to explore the steps of applying ISO 42001 AI Management System with design thinking to link up United Nations Sustainable Development Goals (UNSDGs) to help organizations with AI ISO 42001 in place for business and social impacts beyond 2030. Based on nvivo analysis on seven selected AI compliance and ISO 42001 documents with contents based in service industries, Hong Kong, the 3 key factors for Values generated by AI ISO 42001 (974 references) are :1) SDG9 Innovations with Technology (592 references), 2) SDG16 Institutional and Economic Peace (301 references), and 3) SDG17 Partnership with Trust Certification. This is managerial relevant to nurture the service industries, for example, education, finance and logistics to apply ISO 42001 AI compliance for developing a trust with Certification Culture on top of ISO 9001 QMS, ISO 26000 CSR and ISO 53001 SDG guidelines. It is expected to have qualitative interview results, case studies, and surveys to echo the key findings in this paper for Sustainable Development with standardization.